FROM CUSTODY TO CONTROL: A BRIEF HISTORICAL ANALYSIS OF THE EMERGENCE OF IMPRISONMENT AS A MEANS OF PUNISHMENT - Celestino, Bruno de Omena; de Souza, João Arthur Alves (Seven Editora, 2026)
The theme of imprisonment is a contemporary reality, present in both public and private debate and at various levels of social life. Due to the significant presence of this issue in social discourse, the impression is created that imprisonment as punishment has been part of this institution since its earliest records. In fact, places of confinement have existed since Antiquity, being observed in Egyptian, Mesopotamian, Hellenic, and Roman civilizations, extending into the Middle Ages. However, during this period, prisons served primarily as a means of custody, with rare examples of imprisonment having punitive purposes. At the end of the Middle Ages, some monastic orders of the Roman Catholic Church began to use confinement in cells as a means of discipline and correction of clergy, and it was occasionally applied to laypersons as punishment for the commission of offenses regarded as serious in light of Catholic dogma. Only in the Modern period did the first prison facilities begin to acquire new functions, as a result of changes in the economic and social system.DOI: https://doi.org/10.56238/sevened2026.008-020